Finnish Poverty: A Cross-National Comparison - Veli-Matti Ritakallio (Luxembourg Income Study (LIS), 1994)
The Finnish welfare state is examined in contrast to Sweden, and the public policy of the US and UK. Analyses presented provide strong evidence of the capability of the Nordic welfare model in the equitable alleviation of poverty among all sections of the population
Keywords: 330; Armut; Finnland